A new species of the genus Thrips (Thysanoptera, Thripidae) from the Malagasy Region - Goldarazena, Arturo; Dianzinga, Niry T.; Frago, Enric; Michel, Bruno; Reynaud, Philippe (Zootaxa, 2020)
The genus Thrips comprises 296 species (ThripsWiki 2019) and is the largest of all Terebrantian genera. The only other Thysanopteran genera comparable in size are the phlaeothripids Haplothrips and Liothrips. Species of Thrips can be found in flowers and on leaves of a wide variety of plants from grasses to trees. Most of them are beneficial pollinators (Garcia-Fayos & Goldarazena 2008; Eliyahu et al. 2015), while others are pests and cause significant economic damage (Mound & Marullo 1996). Some of them are polyphagous and widespread, while others are rarely seen and restricted to one species of plant (Palmer 1992).